2003
DOI: 10.1590/s1516-89132003000300005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distance and its association with heterosis in cacao

Abstract: The efficiency of cacao breeding program can be increased by choosing superior crosses to be made between divergent clones. We assessed the genetic distance among five clones with RAPD data (genetic distance - GD) and with yield component data (Mahalanobis distance - MD). The clones were evaluated in a diallel, during five years, for five yield components. A total of 130 RAPD bands were scored. GD and MD were used to determine the correlation between genetic distances among clones and the performance of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 36 publications
2
25
0
3
Order By: Relevance
“…This suggests that high levels of heterozygosity provide advantages to progeny trees for growth characteristics. A similar result was reported by Dias et al (2003), who observed a significant positive correlation between the genetic distances of parents and performances of the progenies for yield traits in cacao. Moreover, significant correlations of a quadratic equation between the genetic distance of parents and height or basal diameter were established in Liriodendron (Li and Wang, 2002) and poplar (Li et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that high levels of heterozygosity provide advantages to progeny trees for growth characteristics. A similar result was reported by Dias et al (2003), who observed a significant positive correlation between the genetic distances of parents and performances of the progenies for yield traits in cacao. Moreover, significant correlations of a quadratic equation between the genetic distance of parents and height or basal diameter were established in Liriodendron (Li and Wang, 2002) and poplar (Li et al, 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, with respect to forest trees, delays before assessing individual performances are long, and a strategy for predicting heterosis before making the crosses and thereby reducing the number of combinations to be tested would be particularly desirable. Many observations and studies consistently provided evidence that there is a correlation between the genetic distance of parents and progeny performance or heterosis for most crops (Zhang et al, 1996(Zhang et al, , 2007Hale et al, 2007;Devi and Singh, 2011;Benin et al, 2012) and several forest trees (Vaillancourt et al, 1995;Kopp et al, 2002;Dias et al, 2003). In these studies, genetic distances were estimated by molecular markers involving restriction fragment length polymorphism, random amplified polymorphic DNA, simple sequence repeat, amplified fragment length polymorphism (AFLP), sequence-related amplified polymorphism (SRAP), and inter-simple sequence repeat (ISSR).…”
Section: Introductionmentioning
confidence: 99%
“…Clair and Kleinschmit (1986) emphasized that in forest tree breeding, this information was useful to distinguish genotypes for specific environments, but if all environments tested was in one planting zone, and each one represented the same proportion of area to be planted, then this information was irrelevant. Selection based on the overall mean was all that was necessary to assure the largest overall gains (Dias et al, 2003). Therefore the genotypes IAN 6721, IAC 313 and IAC 308 could be considered superior in future breeding programs in order to incorporate stability for rubber yield.…”
Section: Resultsmentioning
confidence: 99%
“…Entre estes, os marcadores isoenzimáticos permitem o estudo de um número limitado de loci, enquanto os marcadores do tipo RFLP (restriction fragment length polymorphism), AFLP (amplified fragment length polymorphism), e VNTR (variable number of tandem repeats) são caros, laboriosos e geralmente necessitam de marcação radioativa. Os marcadores do tipo RAPD (random amplified polymorphic DNA) (Williams et al, 1990) superam estas limitações, uma vez que muitos loci podem ser estudados simultaneamente e, associados à possibilidade de utilização de vários iniciadores, garantem a análise de uma amostra significativa de todo o genoma (Dias et al, 2003).…”
Section: Introductionunclassified
“…Marcadores moleculares RAPD têm sido utilizados para estudos de variabilidade genética (Subramanian et al, 2000;Raina et al, 2001;Xavier et al, 2005) para identificação de espécies (Martin et al, 1997), para monitorar a eventual transferência de material genético de espécies diplóides selvagens para o amendoim cultivado (Garcia et al, 2006), para determinar o grau de associação entre a distância genética entre parentes e a performance dos seus híbridos (Dias et al, 2003), e para construção de mapas genéticos de ligação (Menéndez et al, 1997). A técnica do RAPD pode ser eficaz na redução do número de acessos analisados, uma vez que permite a identificação de acessos contrastantes (Xavier et al, 2005).…”
Section: Introductionunclassified